Implementasi Google Speech API Pada Aplikasi Koreksi Hapalan Al-Qur'an Berbasis Android - Ariyan Zubaidi; Affandy Akbar; Ario Yudo Husodo (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
Muroja’ah is a method of repeating new memorization and old memorization that be heard to other people. This method is very popular in Indonesia. In order to make the learning process isn’t boring, it is required a learning media that can be used anytime, one of them are using Android application. The research describes how to build a Qur’an recitation correction application based on Android and integrate it with Google Speech so that application built more interesting and interactive with users. Google Speech be integrate as voice input media, users requested recite Qur’an verses then Google Speech will convert their voice to text. Text result obtained then matched with text in source code. Result of testing the accuracy of Google Speech implementation on this application it’s 100%, that means it’s been as expected.